Why was the Paraná flood of 2016 weaker than that of 1998?. (4th July 2019) - Antico, Andrés; Diaz, Henry F.
Abstract: Although the 2015–2016 El Niño was expected to cause a severe Paraná River flood similar to that associated with the 1997–1998 El Niño, the Paraná flood of 2016 was considerably weaker than that of 1998. Here we explain this by analysing Paraná discharge data (1904–2017) to assess the contributions of discharge cycles with different frequencies and with different associated climate modes to the formation of the 1998 and 2016 floods. We found that the 2016 flood was relatively weak mainly because the following Paraná discharge cycles contributed less to form the 2016 flood than to form the 1998 flood: (a) a 3–5‐year cycle linked to El Niño/Southern Oscillation (ENSO), (b) a 9‐year cycle related to the North Atlantic Oscillation (NAO), and (c) a 31–85‐year cycle associated with the Interdecadal Pacific Oscillation (IPO). This finding suggests that, besides ENSO, two other climate modes (NAO and IPO) may have acted to weaken the 2016 flood. Abstract : Contributions of the cycles and trend of Paraná River discharge to the 1998 and 2016 Paraná floods. These contributions reveal that the 2016 flood was relatively weak mainly because the following discharge cycles contributed less to form the 2016 flood than to form the 1998 flood: (a) a 3–5‐year cycle linked to El Niño/Southern Oscillation, (b) a 9‐year cycle related to the North Atlantic Oscillation, and (c) a 31–85‐year cycle associated with the Interdecadal Pacific Oscillation.